2015
DOI: 10.1111/jpi.12248
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin attenuates impairments of structural hippocampal neuroplasticity in OXYS rats during active progression of Alzheimer's disease‐like pathology

Abstract: Translational research on Alzheimer's disease (AD) has often focused on reducing the high cerebral levels of amyloid-β (Aβ) as a key characteristic of AD pathogenesis. There is, however, a growing body of evidence that synaptic dysfunction may be crucial for the development of the most common (sporadic) form of AD. The applicability of melatonin (mainly produced by the pineal gland) to the treatment of AD is actively evaluated, but usually, such studies are based on animal models of early-onset AD, which is re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
53
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 79 publications
8
53
0
Order By: Relevance
“…2B) and the endoplasmic reticulum, decreased specific area of lysosomes and vacuoles, and slightly but not significantly decreased the specific area of the Golgi complex (Table S1). These data corroborate previous reports of neuronal loss and neurodegenerative changes in the hippocampus of OXYS rats at this age [31] and indicate that SkQ1 treatment prevented the neuronal loss and progression of neurodegeneration in these rats.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…2B) and the endoplasmic reticulum, decreased specific area of lysosomes and vacuoles, and slightly but not significantly decreased the specific area of the Golgi complex (Table S1). These data corroborate previous reports of neuronal loss and neurodegenerative changes in the hippocampus of OXYS rats at this age [31] and indicate that SkQ1 treatment prevented the neuronal loss and progression of neurodegeneration in these rats.…”
Section: Resultssupporting
confidence: 92%
“…3E). Further analyses of the ultrastructural state of pyramidal neurons in the hippocampal CA1 region of the rats revealed significant changes (similar to those showed recently [31]) in the structural organization of the nucleus, nucleolus, Golgi complex, endoplasmic reticulum (Fig. 3F) and mitochondria (Fig.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Furthermore, in aged 22-month old wild-type mice with significantly impaired spatial cognition, melatonin improved cognitive performance by reducing cerebral amyloid burden through altered protein-cleaving secretase expression [97]. In addition, some studies showed that melatonin promotes hippocampal neuroplasticity and stimulates the proliferation and differentiation of neural stem cells in vitro and in vivo [98,99,100]. A number of studies have also demonstrated protective effects of melatonin on the BBB.…”
Section: Antioxidants Cognitive Decline and Blood-brain Barriermentioning
confidence: 99%
“…However, the action of melatonin on cognitive performance may vary between MT 1 and MT 2 signaling as a MT 2 receptor deletion results in impairments in hippocampal long-term memory (Larson et al 2006). In Alzheimer's disease models, melatonin or MT 2 agonists appear to have a therapeutic effect on cognitive performance and hippocampal neuroplasticity (Bahna et al 2014;Ali and Kim 2015;Stefanova et al 2015). While melatonin has the potential to link the circadian system with memory and performance, the actions of melatonin may vary with circadian phase, task specificity, or receptor signaling.…”
Section: Mechanisms Linking the Circadian Clock And Memorymentioning
confidence: 99%